Neighborhoods and Self-Government Bodies of Citizens in the Formation of a Democratic Society - Seytzhanova Ulbosin Kudaybergenovna (Drugs and Cell Therapies in Hematology, 2021)
The article discusses the role of makhallas and citizens’ self-government in the formation of a democratic society in Uzbekistan, the restoration of democratic self-government in Uzbekistan during the years of independence, the role of makhallas in democratic decision-making and social protection.